Photographic Analysis of Facial Soft Tissue by Angular and Proportional Measurements in Adult Pakistani Population: Analysis on Pakistani Facial Tissues - Aziz, Anum; Khalid , Qasim; Nafees, Muhammad Fayyaz; Ata, Saadia; Haroon, Kashif; Habib, Nida (Pakistan Journal of Health Sciences, 2024)
An important requisite of orthodontic treatment is achieving well balanced, pleasant face. Precise diagnosis and treatment planning, on facial hard and soft tissue norms basis, is fundamental for that purpose. Objective: To use photogrammetry technique on standardized photographs, and determination of mean angular and proportional parameters defining characteristics of facial soft tissue, on an adult Pakistani population. Methods: A cross sectional study, on 78 subjects from OPD and students of FMH College of Medicine and Dentistry, were selected. Data were entered and SPSS 2.0 was used for analysis. Mean and standard deviations were used for the quantitate variables used in the study. To control confounders with respect to age and gender, stratification was done and independent t-test was used, taking statistically significant p-value at ≤ 0.05. Results: All parameters were statistically insignificant on the basis of gender and age. The average values of nasolabial angle, angle of facial convexity and facial height proportion were greater in males than in females. The mean values of mentolabial angle, lower face to total face height and facial index were found to be greater in females as compared to males. Conclusions: This study concluded that gender and age based average values for angular and proportional parameters should be used while planning cases for Pakistani population for orthodontic treatment.